Rogers' Three Core Conditions: The Other Side of the Coin - Setiawan, Jenny Lukito (ANIMA Indonesian Psychological Journal, 2008)
This paper aims to show that the three core conditions proposed by Carl Rogers are impor- tant not only for therapeutic change, but also for attracting people to enter therapeutic or helping rela- tionships. By showing the results of a study investigating factors encouraging students in seeking cer- tain people for help, this paper argues that there is other side of the three core conditions declared by Rogers. A multi-method design was adopted in this study. A questionnaire measuring students’ selec- tion of helpers was distributed to 1,279 students. This was followed by individual semi-structured in- terviews (n = 32) and focus groups with students (n = 4 groups). Findings in the present study suggest that people would seek help from those who are perceived as having understanding, acceptance and congruence. Understanding, acceptance and congruence are essential not only for facilitating personal growth, but also for inviting people to enter helping relationships. Artikel ini bertujuan untuk menunjukkan bahwa tiga kondisi inti yang dikemukakan oleh Carl Rogers penting tidak hanya untuk terjadinya perubahan terapeutik, tetapi juga untuk menarik orang memasuki relasi pertolongan atau relasi terapeutik.Dengan memaparkan hasil dari suatu studi yang meneliti faktor-faktor yang melandasi pemilihan penolong pada mahasiswa, artikel ini menun- jukkan bahwa tiga kondisi inti yang dideklarasikan oleh Rogers memiliki sisi lain. Studi ini meng- gunakan desain multi-method. Kuesioner yang mengukur pemilihan sumber penolong disebarkan ke- pada 1279 mahasiswa. Hal ini dilanjutkan dengan wawancara semi terstruktur terhadap 32 maha- siswa serta 4 FGD. Hasil menunjukkan bahwa individu akan mencari pertolongan pada seseorang yang dianggap memiliki pemahaman empatik, penerimaan dan kongruensi.Pemahaman empatik, pe- nerimaan dan kongruensi sangat penting tidak hanya untuk memfasilitasi terjadinya pertumbuhan pri- badi, tetapi juga untuk mengundang orang untuk memasuki relasi pertolongan.